Sharp size-selective catalysis in a liquid solution over Pd nanoparticles encapsulated in hollow silicalite-1 zeolite crystals - Wei, F.; Liu, Jian; Zhang, Q.; Zhang, Y.; Zhang, X.; Cao, C.; Song, W. (Royal Society of Chemistry, 2016)
© 2016 The Royal Society of Chemistry. A lab-in-a-shell method was designed to prepare Pd nanoparticles encapsulated in hollow silicalite-1 zeolite crystals for size-selective catalysis in liquid solution. Due to the pore size limitation of the microporous silicalite-1 shell (0.53 × 0.56 nm), the catalyst showed high activity in the hydrogenation of 3-methyl-2-butenal (0.38 × 0.62 nm) and cinnamaldehyde (0.54 × 0.92 nm), but no activity for 3,3-diphenylacrylaldehyde (0.81 × 1.0 nm).